Estimating the impact of immigrants on the host country social security system when return migration is an endogenous choice - Murat G. Kirdar (Institute for the Study of Labor (IZA), 2010)
In this paper, I estimate the fiscal impact of immigrants on the German pension insurance (PI) and unemployment insurance (UI) systems when return migration is an endogenous choice. For this purpose, I develop a dynamic stochastic model of joint return migration and saving decisions that accounts for uncertainty in future employment and income and estimate this model using a longitudinal data set on immigrants from five different source countries. I find that allowing for the endogeneity of the return decision makes a substantial difference in the net gain of the PI and UI systems from immigrants. Exogenous return migration - which has been the practice of the literature so far - underestimates the net gain for almost all demographic groups and the amount of underestimation is remarkable for several demographic groups. In addition, age-at-arrival profiles of net contributions of immigrants - which form the basis of suggestions on selective immigration policies in the literature - are rotated significantly. Finally, a counterfactual policy experiment in which cash bonuses are provided conditional on return to unemployed immigrants turns out be ineffective in terms of reducing the burden on the state coffers for most demographic groups.
Keywords: J61; D91; H55; J65; J68; 330; Immigrant workers; life cycle models; saving; social security; public pensions; unemployment insurance; public policy; Migranten; Ausländische Arbeitskräfte; Sparen; Rückwanderung; Lebenszyklus; Gesetzliche Rentenversicherung; Arbeitslosenversicherung; Sozialversicherungsfinanzierung; Deutschland